Analisis Strategi Promosi Digital Produk OEM Tisu di PT Infinity Blessing Indonesia - Ratna Nur Lestari; Muhammad Syihabuddin (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the digital promotion strategy of OEM tissue products at PT Infinity Blessing Indonesia. In the digital era, effective promotion is essential for building brand awareness and expanding business-to-business (B2B) networks. The study aims to identify the current digital promotion practices, challenges faced, and strategies to optimize promotional performance. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation involving two key informants from the human resources and product design divisions. The findings indicate that the company has implemented digital promotion through its website, email marketing, and WhatsApp Business, but social media utilization remains limited to Instagram with low engagement. The company’s strengths lie in product customization flexibility, consistent quality, and responsive communication with business partners, while weaknesses include low brand awareness and minimal digital advertising efforts. The research implies that strengthening digital branding, optimizing social media platforms, and adopting paid digital advertising such as Google Ads and LinkedIn Ads can enhance competitiveness and visibility in the B2B market.